ANALISIS TOTAL QUALITY MANAGEMENT DI TK DHARMA LOKA I PEKANBARU - Riana Riana; Azhar Azhar; Sri Kartikowati (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2022)
This research is motivated by the increasing demand for quality education in PAUD institutions along with the increasing growth of PAUD schools in the city of Pekanbaru. With the growth of PAUD which is more than 5 percent per year, quality competition in the world of education is inevitable. Consumers, in this case, parents/guardians of course choose schools that are considered superior, which can create competent students in the future. One way to improve the quality of education is by implementing Total Quality Management so that schools can provide satisfying services that exceed the needs of consumers. For schools especially those who want to go to international standard schools, the use of Total Quality Management is the best choice made to improve quality. This is because by using Total Quality Management, the school will have clear guidelines for the expected quality. Taking a model from the TK Dharma Loka 1 in Pekanbaru that has implemented Total Quality Management, the author tries to analyze it using descriptive qualitative methods to see the extent to which the role of Total Quality Management is to improve school quality. With this research expected, other schools are encouraged to implement Total Quality Management in their schools, so that the expected quality can be achieved and Pekanbaru in particular is ready to enter the era of the education industry in this global age.